Indonesian EFL lecturers’ positive perceptions and adaptive strategies in implementing authentic assessment for sustainable education: Mixed-methods study - Lumintang, Sheline Feranda; Kuswandono, Paulus (Journal of English Language Teaching Innovations and Materials (Jeltim), 2025)
Authentic assessment (AuA) is emerging as an alternative that has its own appeal, especially in the context of sustainability education. Although numerous studies have investigated how authentic assessment is perceived and practiced in EFL higher education within Indonesia, studies which connects AuA practices with sustainability education are still underrepresented. AuA practices can promote students’ critical thinking and problem-solving skills and is increasingly recognized for its potentials to promote meaningful and effective learning, especially in English as a Foreign Language (EFL) classrooms. This study investigates two key questions: (1) how EFL lecturers perceive and address the challenges of implementing authentic assessment in sustainability education; and (2) what instructional strategies lecturers can use to implement authentic assessment in sustainability education. Using a mixed-methods approach, survey data and follow-up interviews were collected from 30 English lecturers of various universities in Indonesia. The quantitative data shows that lecturers view authentic assessment as a relevant and effective tool. However, the data highlighted two key challenges: limited time and pressure from institutional expectations. Qualitative results further reveal how lecturers design assessment tasks, reflect on their practice, and integrate sustainability values into their teaching, while pointing to the need for institutional support. Overall, the study highlights lecturers’ positive perceptions and emphasizes the importance of external support to ensure authentic assessment effectively promotes context-relevant learning and sustainability education. How to cite this paper: Lumintang, S. F., & Kuswandono, P. (2025). Indonesian EFL lecturers’ positive perceptions and adaptive strategies in implementing authentic assessment for sustainable education: Mixed-methods study. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(2), 38-58. http://dx.doi.org/10.26418/jeltim.v7i2.96334